Sistem Pendukung Keputusan Pemilihan Customer Service Terbaik Menggunakan Metode WASPAS (Weight Aggregated Sum Product Assesment) - Robiah Al-Adawiyah; Ritonga, Devi; Muhammad Syahrizal (Journal of Decision Support System Research, 2024)
Customer service plays a very important and problematic role in forming the image of a company or organization, so with the help of customer service every customer or consumer can ask and use the information provided both about services and goods. Both verbal and non-verbal communication methods in customer service have a significant impact on the image of a company or organization. In order for the company's services to be provided optimally and maximally to customers, everyone must support each other. Qualification standards have a significant impact on excellent customer service in a company or organization. Effective customer service plays a key role in building good customer relationships and ensuring their satisfaction. Therefore, choosing the right customer service is important for companies as well as organizations. So we need a Decision Support System (SPK) in solving this problem. So that a Decision Support System (DSS) is needed in solving this problem. In this study using the Weight Aggregated Sum Product Assessment (WASPAS) method. This method uses an approach to selecting the highest and lowest values ??that can be optimized to provide more accurate results. Several methods on decision support systems in producing the best alternatives include SAW, WP, AHP, MOORA, MOOSRA and OCRA. WASPAS (Weight Aggregated Sum Product Assessment) is one of the methods that can do this to reduce errors or to optimize the evaluation of the selection of the highest and lowest values. This method is a unique combination of the MCDM approach, namely the weighted numerical model (WSM) and the Product Weight Model (WPM). One of the problems faced in the selection of customer service is due to the large number of people who register, therefore to determine the best customer service acceptance the company conducts data collection by determining the criteria and weights that must be met to carry out the calculations, so that the best alternative results can be obtained. it can be concluded that the WASPAS (Weight Aggregated Sum Product Assessment) method is very appropriate to use in selecting the best customer service. Evidenced by the results being in alternative (A1), namely Daughter as the best preference with a value of 3.19755, so that a decision support system with the WASPAS (Weight Aggregated Sum Product Assessment) method can help a company or a particular brand in choosing the best customer service to work together in companies or other agencies.